EFEKTIFITAS KONSELING KELOMPOK ADLERIAN DALAM MENGATASI PERILAKU EGOSENTRIS PADA SISWA REMAJA - Kristiani, Lidya Novi; Widodo, Bernardus (Educatio Vitae, 2015)
This study aims to determine the effectiveness of Adlerian group counseling to overcome egocentric behavior on adolescent students. The population in this study were students of class VIII D 11 Madison Junior High School, school year 2013/2014 the number of 10 students consisting of 5 students in the experimental group and a control group of 5 students. Collection file techniques in this study using a scale egocentric behavior and direct observation in the form of a check list. This study used an experimental method with a pure experimental design. And using the pre-test and post test design with a control goup kind treatment. In this study there are two groups : the control group and the experimental group ( traitment ) treatment given Adlerian group counseling. The control group was given left without treatment. Then both groups were given a post-test. Adlerian group counseling meetings held as many as 5 times. File analysis of the measurements before and after treatment using the Adlerian group counseling techniques to One Way ANOVA to study 10 subjects, showed that : the experimental group arithmetic average (means ) pre-test was 18.456 with a minimum score of 91 and a maximum score of 116 probability 0.003 and the arithmetic mean (means) post-test is 8.253 with a minimum score of 50 and a maximum score of 99 probability of 0.021, with a probability of homogeneity in the results of pre-test 0.444 and post-test 0.107 . Thus there is a decrease in scores after treatment rendered (traitment). From these data it can be concluded that the Adlerian group counseling proven effective in overcoming egocentric behavior on adolescent students . Keywords : self-centered behavior , Adlerian group counseling